Magid Glove and Safety Manufacturing Co. - Ward, John L., 1945- (SAGE Knowledge. Cases., 2005)
The case examines the strategies and protocols used by the Cohen family members to run Magid Glove & Safety Manufacturing and how these strategies enabled the company to thrive and for the family members to come to an agreement about the future of the company.